COBALT-CATALYZED CARBONYLATIVE POLYMERIZATION OF UNDEC-10-EN-1-OL - Pratiwi Indriyani, Nova
Carbonylative polymerization of undec-10-en-1-ol catalyzed by HCo(CO)4 to produce polydodecyloate, an aliphatic polyester, has been investigated. The formation of an active catalyst, HCo(CO)4, via hydrogenation of Co2(CO)8 and copolymerization of undec-10-en-1-ol/CO were conducted in a high pressure autoclave by a one-pot method. The reaction was carried out with CO/H2 pressure of 22 bar, for 18 h, at 160 °C, using Co2(CO)8 of 1.4 mol% to generate solid polymer with catalyst activity of 486 g.mol cat-1.h-1. The product was characterized by FTIR, 1H-NMR and 13C-NMR. The carbonyl moety of polyester was exhibited at 1716 cm-1 by infrared which was supported by the 13C resonance at 174 ppm. Theoretical investigation has been studied for an associative mechanism pathway and olefin 2,1 insertion of undec-10-en-1-ol to HCo(CO)4 using density functional theory (DFT) B3LYP method and cc-pVDZ basis set for all atoms. Calculation results showed that activation energy of an associative pathway was lower than a dissociative pathway. However, the calculation of theoretical reaction rate for dissociative pathway was much higher than the associative one. The observation of olefin-2,1 insertion showed that the activation energy of olefin-2,1insertion step was higher than the olefin-1,2 insertion step. These calculation results agreed with the previous work which showed the more formation of aliphatic polydodecyloate than the branched polydodecyloate .